2003
DOI: 10.1093/jn/133.4.1158
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of Food with Enterococcus faecium (SF68) Stimulates Immune Functions in Young Dogs

Abstract: The gut microflora play a crucial role in several physiologic functions of the host, including maturation of the gut-associated lymphoid tissues during the first months of life. Oral administration of probiotic lactic acid bacteria (LAB) modulates the immune system of humans and some laboratory animals. This effect has never been examined in dogs; therefore, our aim was to study the capacity of a probiotic LAB to stimulate immune functions in young dogs. Puppies were allotted to two groups receiving either a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
117
1
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(126 citation statements)
references
References 32 publications
6
117
1
2
Order By: Relevance
“…This is in line with our previous observations that villus length, crypt depth, villus/crypt ratio and villus surface area of the small intestine were greater (P , 0.001 to 0.703) in rats receiving the FDOI diet than in rats fed either the BD or the IOI diet (Balan et al, 2009). Plasma IgA plays an important role in inhibiting allergen absorption (Benyacoub et al, 2003). In this study, plasma IgA concentrations were also greater in rats fed the FDOI diet than in rats fed the BD diet.…”
Section: Discussionsupporting
confidence: 92%
“…This is in line with our previous observations that villus length, crypt depth, villus/crypt ratio and villus surface area of the small intestine were greater (P , 0.001 to 0.703) in rats receiving the FDOI diet than in rats fed either the BD or the IOI diet (Balan et al, 2009). Plasma IgA plays an important role in inhibiting allergen absorption (Benyacoub et al, 2003). In this study, plasma IgA concentrations were also greater in rats fed the FDOI diet than in rats fed the BD diet.…”
Section: Discussionsupporting
confidence: 92%
“…In studies of methotrexate-induced enterocolitis in rats, the administration of Lactobacillus plantarum strain 299v increased colonic and ileal levels of sIgA, and reduced mucosal inflammation (37,38). It has been shown that oral administration of Enterococcus faecium SF68 increases intestinal IgA production in dogs (39).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that serum IgG concentrations in piglets are highly correlated with preweaning mortality (Cabrera et al, 2012). Previous studies have shown that probiotics enhanced immune activity in pigs, dogs and chickens (Benyacoub et al, 2003;Haghighi et al, 2006;Szabó et al, 2009). In the present study, L. fermentum administration resulted in a significant increase in the concentration of immunoglobulins (IgG, IgM and IgA) in piglets at 17 days of life.…”
Section: Discussionmentioning
confidence: 99%